2022
DOI: 10.1037/pas0001123
|View full text |Cite
|
Sign up to set email alerts
|

A field study of acute dynamic risk assessment in individuals convicted of sexual offenses.

Abstract: Acute dynamic risk factors can change over short periods of time, even within days or hours. When making risk assessments of individuals convicted of sexual offenses, it is necessary to consider this rapidity of change, in order to monitor appropriately the recidivism risk and to prevent future crimes. Until now, there is only one instrument-the Acute-2007-which assesses acute risk factors in individuals convicted of sexual offenses. However, the current state of research about its psychometric properties is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Finally, in order to be able to contrast a “pure” actuarial risk assessment approach with other assessment methods, it was necessary to score the VRAG-R retrospectively and to compare these retrospective assessment results with the prospectively made assessments of the expert witness reports. However, as previously published studies about second-generation ARAIs indicated (e.g., Nitsche et al, 2022; Rettenberger et al, 2013;Rettenberger, Rice, et al, 2017), the predictive accuracy of this actuarial approach yielded comparable results independently of the applied research design (i.e., if a retrospective of a prospective data collection procedures was used).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Finally, in order to be able to contrast a “pure” actuarial risk assessment approach with other assessment methods, it was necessary to score the VRAG-R retrospectively and to compare these retrospective assessment results with the prospectively made assessments of the expert witness reports. However, as previously published studies about second-generation ARAIs indicated (e.g., Nitsche et al, 2022; Rettenberger et al, 2013;Rettenberger, Rice, et al, 2017), the predictive accuracy of this actuarial approach yielded comparable results independently of the applied research design (i.e., if a retrospective of a prospective data collection procedures was used).…”
Section: Discussionmentioning
confidence: 61%
“…witness reports. However, as previously published studies about second-generation ARAIs indicated (e.g., Nitsche et al, 2022;Rettenberger et al, 2013;Rettenberger, Rice, et al, 2017), the predictive accuracy of this actuarial approach yielded comparable results independently of the applied research design (i.e., if a retrospective of a prospective data collection procedures was used).…”
Section: Limitationsmentioning
confidence: 59%
See 1 more Smart Citation
“…The items are considered to represent high-risk situations and the current expressions of chronic, risk-relevant factors (Fernandez et al, 2014). The ACUTE-2007 predicts sexual, violent, and any recidivism and adds discriminative ability above that of static risk tools (Hanson et al, 2007; Nitsche et al, 2022). Change in ACUTE-2007 total scores are associated with changes in the likelihood of sexual, violent, and general recidivism (Babchishin & Hanson, 2020; Lee et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…The risk of sexual reoffending is dynamic in nature and varies over time and across contexts (Babchishin & Hanson, 2020;Lussier et al, 2020;Olver & Stockdale, 2020;Nitsche et al, 2022). The NBM-RSR assumes that risk of sexual reoffending:…”
Section: Network-based Model Of Risk Of Sexual Reoffending (Nbm-rsr)mentioning
confidence: 99%